Optogenetics and Chemogenetics - Vlasov, Ksenia (Methods Enzymol, 2018)
Optogenetics and chemogenetics provide the ability to modulate neurons in a type-and region-specific manner. These powerful techniques are useful to test hypotheses regarding the neural circuit mechanisms of general anesthetic end points such as hypnosis and analgesia. With both techniques, a genetic strategy is used to target expression of light-sensitive ion channels (opsins) or designer receptors exclusively activated by designer drugs in specific neurons. Optogenetics provides precise temporal control of neuronal firing with light pulses, whereas chemogenetics provides the ability to modulate neuronal firing for several hours with the single administration of a designer drug. This chapter provides an overview of neuronal targeting and experimental strategies and highlights the important advantages and disadvantages of each technique.